Das latènezeitliche Gräberfeld von Mannersdorf am Leithagebirge, Flur Reinthal Süd, Niederösterreich : Studien zu Phänomenen der latènezeitlichen Kulturausprägungen - Ramsl, Peter C. (2011)
This publication is the first monographic result of the APART project “Migration Phenomena in the Early La Tène Period” and the Austrian Science Fund project “The Celtic cemetery in Mannersdorf (Lower Austria) in the context of east-west cultural contact”. From 1976 to 1984, Heribert Schutzbier and Friedrich Opferkuh from the Mannersdorf Museum, together with the Austrian Federal Department of Sites and Monuments, excavated a total of 96 inhumation and cremation burials from the Early and Middle La Tène periods in the field Reinthal Süd. The artefacts are of high quality, seen primarily in the use of materials such as silver, gold, glass and corals, as well as in their technical workmanship. A major find at the cemetery is a bronze situla, which was imported from northern Italy. Certain areas, like the Middle Rhine, the Champagne or the Balkan, must have been well connected to this Lower Austrian region. An analysis revealed a group of “Lt B1 elite or leading graves”, with persons wearing double foot and hand bands and the graves containing precious metals. In the central Danube region, the size of the necropolis in Mannersdorf am Leithagebirge, with its 96 graves, lies midfield. According to a considered but cautious opinion, it is possible that some of those buried in Mannersdorf were a group of people originating from the area of today’s Switzerland. An equally possible hypothesis is, and this does not contradict the first view, that here members of an “upper class” are represented. Printed with the support of the Austrian Science Fund (FWF).